2017
DOI: 10.3390/app7101011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steel Fiber and Different Environments on Flexural Behavior of Reinforced Concrete Beams

Abstract: Abstract:The main kind of deterioration in marine Reinforced Concrete (RC) structures and other infrastructures is steel bar corrosion due to cracks in concrete surfaces, which leads to the reduction of the load carrying capacity, ductility, and structural safety. It seems that steel fibers can reduce and delay the cracking, and increase the flexural strength and ductility of marine RC structures. To do so, in marine atmosphere and the tidal zone of the Oman Sea and fresh water, the flexural behavior of beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For many years, researchers have been studying the effectiveness of steel fibers on the flexural behavior of RC structural members and it has long been acknowledged that they improved bending moment strength, ductility, failure toughness, and energy absorption capacity. Flexural cracking performance of SFRC beams with longitudinal steel reinforcing bars also appears to be enhanced with increased crack number, reduced crack width and height, restricted crack propagation, and delayed concrete spalling [68,69,70]. It has also been demonstrated that deformed or hook-ended steel fibers with higher aspect ratios can increase cracking resistance, energy dissipation, and ductility index most effectively [71,72].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, researchers have been studying the effectiveness of steel fibers on the flexural behavior of RC structural members and it has long been acknowledged that they improved bending moment strength, ductility, failure toughness, and energy absorption capacity. Flexural cracking performance of SFRC beams with longitudinal steel reinforcing bars also appears to be enhanced with increased crack number, reduced crack width and height, restricted crack propagation, and delayed concrete spalling [68,69,70]. It has also been demonstrated that deformed or hook-ended steel fibers with higher aspect ratios can increase cracking resistance, energy dissipation, and ductility index most effectively [71,72].…”
Section: Introductionmentioning
confidence: 99%
“…It is also noted that, the concrete mix MC have lower compressive strength than the RF0 mix, it is due to the presence of excessive water content due low water absorption of copper slag in the CF0 mix having 100% copper slag tends and Ettringite formation in the copper slag contained concrete. From Figure 7, the flexural strengths found to increase with increase in dosage of crimped steel fibre up to dosage of 1% for both 30 mm and 50 mm fibre due to bridging of fibre at crack and act as crack arrestors and increase in resistance to pulling resistance due to the presence of fibre [50]. Beyond 1% dosage of steel fibre, the Flexural strength tends to decreases due to the presence of extra fibres start to interfere with each other and within the concrete matrix.…”
Section: Compressive and Flexural Strengthmentioning
confidence: 99%
“…The results showed that the presence of these protective jackets that the effect had included effects and changes on the hoop confinement and the high resistance to R.P.C. Former researches such as Bafghi et al [45], Kotsovos et al [46], Soutsos et al [47], Barros and Figueiras [48], and Campione and Mangiavillano [49] had shown that the existence of steel fibers in concrete prevents or delays concrete cover spalling with an increase in the deformation capacity. The compressive, splitting, and flexural strengths rise while adding more amount of steel fibers.…”
Section: Introductionmentioning
confidence: 99%